PENGARUH STRES KERJA TERHADAP KINERJA PEGAWAI PADA MADRASAH ALIYAH NEGERI 2 MODEL PALU - Abdul Jalil (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2020)
This study aims to determine the Effect of Work Stress which includes Environmental Stress, Organizational Stress, andIndividual Stress on the Performance of Civil Servants 2 in the Palu Model. The problem raised in this study is whetherthere is an influence of work stress consisting of Environmental Stress, Organizational Stress, and Individual Stress onthe Performance of Civil Servants 2 in the Palu Model. From the above problem, a research hypothesis is proposed thatit is assumed that work stress which consists of Environmental Stress, Organizational Stress, and Individual Stressaffects the performance of Madrasah Aliyah Negeri 2 Palu Model Employees. This type of research is a verificationstudy, sampling technique using saturated or census sampling. This research was conducted at Madrasah Aliyah Negeri2 Model Palu. The total sample is 51 respondents.To prove this hypothesis, researchers used multiple linear regression analysis. From the results of the study found thereis the influence of work stress consisting of environmental stress (X1), organizational stress (X2) and individual stress(X3) on the performance of employees of MAN 2 Palu Model. This can be seen from the environmental stress (X1)with sig. 0.014, organizational stress (X2) with a sig value of 0.025 and individual stress (X3) with a sig value of 0.038which is smaller than alpha 0.05. The most dominant environmental stress variable has a significant effect on theperformance of MAN 2 Palu Model employees.It is expected that the Leaders of MAN 2 Palu Model should pay attention to environmental, organizational andindividual factors because these three factors can have an effect on employee performance. It is expected that the MAN2 Model Palu Leaders pay attention to, and maintain the stability of work stress caused by environmental,organizational and individual factors through motivating activities such as ESQ, recreation, out bonding, relaxationtime, division of work hours, discussion forums, suggestion boxes and openness of leaders ultimately has implicationsfor optimal employee performance. MAN 2 Model Palu must give extra attention to employees who are in the officeenvironment. Dirty, hot environmental conditions and work demands that are regulated by time make it easier foremployees to experience pressure.